Terapi Aktivitas Senam Ergonomis Untuk Meningkatkan Kemampuan Fungsional Lansia Di Panti Werda Griya Asih Lawang Kabupaten Malang - Swito Prastiwi; Ardina Eka Wahyuningtyas (Jurnal Keperawatan Terapan, 2023)
Various kinds of problems that are often experienced by the elderly such as impaired gross motor and fine motor movements, decreased musculoskeletal function, decreased functional ability and behavior of the elderly towards daily activities. One of the actions to overcome the decline in functional ability is ergonomic exercise activity therapy. This study aims to determine the functional ability of the elderly after ergonomic exercise activity therapy. This case study method is descriptive which is done by interviewing and observing 2 elderly subjects. The research was conducted at the Griya Asih Lawang Nursing Home on 13-25 February 2023, using measurements of the Barthel index, family Apgar, mini mental state examination, and the geriatrics depression scale. The results of the study on 2 subjects after doing ergonomic exercise activity therapy functional abilities increased in physical, social, mental, and emotional aspects. Conclusion Ergonomic exercise activity therapy is effective for improving the functional abilities of the elderly. It is hoped that the subject will carry out regular ergonomic exercise activity therapy at least 3 times a week and for further researchers be able to develop research on ergonomic exercise activity therapy on the functional abilities of the elderly and on the assessment of mental aspects can be deepened by combining other therapies such as Brain Gym.